Long-term Leisure-time Physical Activity and Serum Metabolome - Kujala, Urho M.; Mäkinen, Ville-Petteri; Heinonen, Ilkka; Soininen, Pasi; Kangas, Antti J.; Leskinen, Tuija H.; Rahkila, Paavo; Würtz, Peter; Kovanen, Vuokko; Cheng, Sulin; Sipilä, Sarianna; Hirvensalo, Mirja; et al. (Circulation (New York, N.Y.), 2013)
Long-term physical inactivity seems to cause many health problems. We studied whether persistent physical activity compared with inactivity has a global effect on serum metabolome toward reduced cardiometabolic disease risk. Sixteen same-sex twin pairs (mean age, 60 years) were selected from a cohort of twin pairs on the basis of their >30-year discordance for physical activity. Persistently (≥5 years) active and inactive groups in 3 population-based cohorts (mean ages, 31-52 years) were also studied (1037 age- and sex-matched pairs). Serum metabolome was quantified by nuclear magnetic resonance spectroscopy. We used permutation analysis to estimate the significance of the multivariate effect combined across all metabolic measures; univariate effects were estimated by paired testing in twins and in matched pairs in the cohorts, and by meta-analysis over all substudies. Persistent physical activity was associated with the multivariate metabolic profile in the twins (P=0.003), and a similar pattern was observed in all 3 population cohorts with differing mean ages. Isoleucine, α1-acid glycoprotein, and glucose were lower in the physically active than in the inactive individuals (P<0.001 in meta-analysis); serum fatty acid composition was shifted toward a less saturated profile; and lipoprotein subclasses were shifted toward lower very-low-density lipoprotein (P<0.001) and higher large and very large high-density lipoprotein (P<0.001) particle concentrations. The findings persisted after adjustment for body mass index. The numerous differences found between persistently physically active and inactive individuals in the circulating metabolome together indicate better metabolic health in the physically active than in inactive individuals.